Tertiary treatment of biologically treated palm oil mill effluent (POME) using UF membrane system: effect of WMCO and transmembrane pressure - Oseni, Munirat Idris; Jami, Mohammed Saedi; Muyibi, Suleyman Aremu (2010)
This study evaluate the performance of ultrafiltration UF membrane system in the treatment of biologically treated palm oil mill effluent (POME) by varying the effects of transmembrane pressure and using different molecular weight cut-off (MWCO). Flat sheet polyethersulfone (PES) ultrafiltration membrane of molecular weight cut-off (MWCO) 1kDa and 5kDa were used in this study. Biologically treated POME was subjected to physical pretreatment processes, consisting of coagulation and adsorption units to remove total suspended solids. Transmembrane pressure was varied between 0.5 bar to 1.5 bar and the performance of these membrane systems were assessed in terms of reduction of chemical oxygen demand (COD), color and turbidity in POME. Pretreatment process which consisted of coagulation and adsorption played significant role in reducing COD, colour and turbidity by 97.9%, 99.3% and 99.9% respectively. The highest reduction COD, colour and turbidity occurred at transmembrane pressure of 0.5bar and better permeate quality was obtained with MWCO of 1 kD. The results also showed that UF membrane of MWCO of 5 kDa gave higher flux compared with MWCO of 1kDa.